Modeling on the association between road environment contributory factors and road traffic accidents for Federal Road 2 - Intan Suhana, M. R.; Zulkiple, Adnan; Ismail, Azlina B.H.; Mohd. Ziunizan, Hamzah; Amir Asyraf, Idris (2012)
Road safety research has revealed a number of factors that may lead to road traffic accidents such as the driver's fault, vehicle 's failure and roadway condition and environment. Many studies have been done extensively focu sing on the first two factors and countermeasures always aimed at changing and controlling the human beings in the system.However, road environment also can have strong influences that lead to road crashes for instance the weather and lighting conditions especially when travelling during night time in the raining weather. The possible causes that contribute to those crashes will be poor visibility of lighting, poor sign quality and also might be because of the slippery pavement. Prior to that issue, this study was conducted to examine the association between road environment factors which directly focusing on the travelling periods of time of the day, day of the week and month of the year to the number of road traffic accidents. To achieve this study, a stretch road of 63km Jalan Kuantan - Maran (Federal Road 2) was selected to serve as a study area. It is a dual 2-lane carriageway that forms the backbone of Kuantan road network which experiences high traffic volume as it caters as a main trunk road that link Kuala Lumpur and east coast region. The main data of road accident cases at this study area were obtained from Royal Police Malaysia, Traffic Units. For the purposes of data processing and interpretation, those accidents cases were disaggregated by six similar sections denoted as Section 1 to Section 6. Then, the Correlation and Inferential Analysis of Non- Parametric Test forms the basis for testing the association between each travelling periods of time, day and month to the number of road traffic accidents by using the Statistical Package for Social Sciences (SPSS) Version 12.0. Based on the analysis, the result demonstrated that there was a weak correlation develops on each time of the day, day of the week and also month of the year to the number of road traffic accidents along Jalan Kuantan - Maran (Federal Road 2). Anyhow there is a strong significance value between these factors to the number of accidents. In other words, time, day and month do have influence to the number of accidents along Jalan Kuantan - Maran (Federal Road 2). However, it is recommended that further studies need to be carried out for validation of the result.